Profound hypothermia after adenosine kinase inhibition in A1AR-deficient mice suggests a receptor-independent effect of intracellular adenosine - Eisner, Christoph; Thiel, Manfred (Pflügers Archiv, 2017)
Administration of the nucleoside adenosine has been shown to induce hypothermia in a number of species, an effect mediated predominantly by the adenosine 1 receptor (A1AR) subtype. The present experiments were performed to explore the possibility that the rise of intracellular adenosine levels expected to accompany adenosine administration may contribute to the hypothermic effect of adenosine independent of A1AR activation. Since phosphorylation of adenosine by adenosine kinase (ADK) is causal in the maintenance of low intracellular adenosine, we have examined the effect of ADK inhibition on core body temperature (CBT). Our data show that inhibition of ADK by A-134974 causes a long-lasting deep hypothermia in wild-type mice. Since there was an about 4-fold increase of adenosine plasma levels, experiments were repeated in A1AR−/− mice. ADK inhibition caused deep hypothermia despite the absence of A1AR, although the effect was significantly reduced compared to WT. Furthermore, the dose-dependent hypothermia caused by adenosine administration in WT mice was found to be reduced, but not abolished in A1AR−/− mice. To assess the possible role of A2AR and A3AR activation in our experimental setting, we compared the effects of the agonists CPA (A1AR), CGS21680 (A2AR), and IB-MECA (A3AR) on CBT. Hypothermia induced by CPA was much greater than that caused by CGS21680 or IB-MECA indicating that A1AR activation is the major receptor-dependent pathway for adenosine-induced hypothermia under our experimental conditions. Induction of deep hypothermia by inhibition of ADK, maintenance of this effect in A1AR−/− mice, and maintenance of adenosine-induced hypothermia in A1AR-deficient mice suggest that a receptor-independent action of adenosine requiring intact function of adenosine kinase contributes importantly to the hypothermia induced by adenosine.